Building the Iowa Data Drive: A Participatory Approach to Developing Early Childhood Indicators for State and Local Policymaking - Rouse, Heather; Zanti, Sharon; Kim, Hannah; Dorius, Cassandra; Abraham, William; Chighladze, Giorgi (International Journal of Population Data Science, 2025)
Introduction Public service leaders face increasing challenges using data effectively due to program silos, limited resources, and the increasing complexity of data. To address these challenges, Iowa's Integrated Data System for Decision-Making (I2D2) partnered with state and local leaders in early childhood to curate key indicators and develop population-level data tools and training to promote policy and practice improvements. Methods We relied on a mixed-methods, participatory approach to understand early childhood data and reporting requirements and how state and local leaders leverage data to meet these requirements and inform decisions. We conducted a Data Landscape Overview consisting of interviews, surveys, document review, and meetings with state and local leaders. Public deliberation facilitated iterative feedback and collective decision-making through stakeholder discussions. Results Our participatory approach resulted in three actions to improve data collection and use within Iowa's early childhood system: curating a set of early childhood indicators; developing training and strategic planning tools for effective data use; and building the Iowa Data Drive (IDD), an interactive data portal for accessing key early childhood indicators and population-level insights. Conclusions A robust IDS can promote systems change when grounded in strong partnerships, phased implementation, and a commitment to clear communication. By centering local voices and fostering trust, we developed indicators and tools that support data-informed decisions and improved services for young children and their families.